PENINGKATAN KUALITAS PELAYANAN MELALUI SURVEI KEPUASAN MASYARAKAT DI PUSKESMAS PARANGLOE - Irman, Arif Aprilia Jaya Ganda; Fitri Azmi, Ilima (ADMIT: Jurnal Administrasi Terapan, 2023)
Public service as the provision of services to the wider community is a big demand that must be met by all countries, including Indonesia. Public services are not only present and implemented without being followed by quality improvement. It takes a good response from the community towards these services to be categorized as excellent service. The provision of health service facilities is also one form of public service that can be provided by the government. One of the institutions providing health services in Indonesia that often found is Public Health Center. Parangloe Public Health Center is one of the agencies that provide health care facilities. To obtain more complete or comprehensive results, this study applied mixed methods. Based on the results of research for the nine elements of services provided, Parangloe Public Health Center obtained an IKM score of 76.25, or in the GOOD category. However, there are still elements with bad service values so the Parangloe Public Health Center needs to improve and improve health services in order to achieve community satisfaction.